Time Distortions in Mind : Temporal Processing in Clinical Populations - Argiro Vatakis; Melissa Allman (Brill, 2015)
Time Distortions in Mind brings together current research on aspects of temporal processing in clinical populations, in the ultimate hope of elucidating the interdependence between perturbations in timing and disturbances in the mind and brain. Such research may inform not only typical psychological functioning, but may also elucidate the psychological consequences of any pathophysiological differences in temporal processing. This collection of current knowledge on temporal processing in clinical populations is an excellent reference for the student and scientist interested in the topic, but it also serves as the stepping-stone to share ideas and push forward the advancement in understanding how distorted timing can lead to a disturbed brain and mind or vice versa.Contributors to this volume: Ryan D. Ward, Billur Avlar, Peter D Balsam, Deana B. Davalos, Jamie Opper, Yvonne Delevoye-Turrell, Hélène Wilquin, Mariama Dione, Anne Giersch, Laurence Lalanne, Mitsouko van Assche, Patrick E. Poncelet, Mark A. Elliott, Deborah L. Harrington, Stephen M. Rao, Catherine R.G. Jones, Marjan Jahanshahi, Bon-Mi Gu, Anita J. Jurkowski, Jessica I. Lake, Chara Malapani, Warren H. Meck, Rebecca M. C. Spencer, Dawn Wimpory, Brad Nicholas, Elzbieta Szelag, Aneta Szymaszek, Anna Oron, Melissa J. Allman, Christine M. Falter, Argiro Vatakis, Alexandra Elissavet Bakou